Racial Differences in Insular Connectivity and Thickness and Related Cognitive Impairment in Hypertension - Chand, Ganesh B.; Wu, Junjie; Qiu, Deqiang; Hajjar, Ihab (Frontiers in Aging Neuroscience, 2017)
Hypertensive African-Americans have a greater risk of cognitive impairment than hypertensive Caucasian-Americans. The neural basis of this increased risk is yet unknown. Neuroimaging investigations suggest that the normal neural activity comprises complex interactions between brain networks. Recent studies consistently demonstrate that the insula, part of the salience network, provides modulation effects (information flow) over the default-mode and central-executive networks in cognitively normal subjects, and argue that the modulation effect is declined in cognitive impairment. The purpose of this study is to examine the information flow at the nodes of three networks using resting state functional MRI data in cognitively impaired hypertensive individuals with the African-Americans and the Caucasian-Americans races, and to compare the thickness of impaired node between two racial groups. Granger causality methodology was used to calculate information flow between networks using resting state functional MRI data, and FreeSurfer was used to measure cortical thickness from T1-weighted structural images. We found that negative information flow of the insula in both African-Americans and Caucasian-Americans, which was in contrast with previously reported positive information flow in this region of normal individuals. Also, significantly greater negative information flow in insula was found in African-Americans than Caucasian-Americans (Wilcoxon rank sum; Z = 2.06; p < 0.05). Significantly lower insula thickness was found in African-Americans compared with Caucasian-Americans (median = 2.797 mm vs 2.897 mm) (Wilcoxon rank sum; Z = 2.09; p < 0.05). Finally, the insula thickness correlated with the global cognitive testing measured by Montreal cognitive assessment (Spearman’s correlation; r = 0.30; p < 0.05). These findings suggest that the insula is a potential biomarker for the racial disparity in cognitive impairment of hypertensive individuals.